Sexual orientation and the W.I. constitution - McIntosh, Simeon C.R.
Aims to establish the view that the laws criminalising homosecual intimacy among consenting adults in private are in violation of the fundamental rights provisions articulated in the West Indian constitution, and should therefore be struck down by the Caribbean Court of Justice, should the Belizean case, challenging the constitutionality of Belize's legislation, come to it on appeal.\n